TEKANAN EKONOMI DAN HARAPAN MASA DEPAN PADA KELUARGA LANJUT USIA PENGRAJIN SANGKAR BURUNG DI KABUPATEN BANDUNG - Sudrajat, Ajat (Pekerjaan Sosial, 2012)
AbstractEconomic strain in the form of limited job opportunities, high prices of basic commodities, low levels of income and intense competition in the employment and livelihood; suspected of having links with the expectations of the future family life. The results of this research indicated that economic strain had no impact on future expectations of elderly craftsmen; attitudes and their outlook towards life and living, jobs and their current circumstances. Although the craftsmen have been elderly, but they still have optimistic views, self-confidence, a belief held, the way to solve the problems, viewing that: life is work and work, and motivation is never recede. Keywords: elderly families bird cage craftsmen-economic strain-future expectations AbstrakTekanan ekonomi berupa sempitnya lapangan pekerjaan, mahalnya harga kebutuhan pokok, rendahnya tingkat pendapatan dan ketatnya persaingan dalam pekerjaan dan penghidupan; diduga mempunyai hubungan dengan harapan terhadap kehidupan masa depan keluarga. Hasil penelitian ini menunjukkan, tekanan ekonomi tidak berdampak luas terhadap harapan masa depan pengrajin sangkar burung lanjut usia. Sikap dan pandangan mereka terhadap hidup dan kehidupan, pekerjaan, dan keadaan mereka walaupun sudah lanjut usia, tetapi mereka mempunyai pandangan optimistik, rasa percaya diri, keyakinan yang dimiliki, cara memecahkan masalah,  pandangan: hidup adalah bekerja dan bekerja, dan motivasi tidak pernah surut. Kata kunci: keluarga lanjut usia, perajin sangkar burung, tekanan ekonomi, harapan masa depan